In situ-formed flexible three-dimensional honeycomb-like film for a LiF/Li3N-enriched hybrid organic–inorganic interphase on the Li metal anode. (25th May 2021) - Ma, Chengwei; Mu, Ge; Lv, Haijian; Liu, Chengcai; Bi, Jiaying; Fu, Jiale; Mu, Daobin; Wu, Borong; Wu, Feng
Abstract : An in situ formed flexible three dimensional honeycomb-like PTFEMA film is designed to construct LiF/Li3 N-riched hybrid organic–inorganic interphase. Abstract : The solid–electrolyte interphase (SEI) plays an important role in stabilizing lithium metal anodes for high-energy storage batteries. However, SEI between the lithium metal anode and liquid electrolyte is usually unstable due to nonuniform Li deposition. A stable SEI is considered to be an effective way to control the interfacial structure and improve the stability of lithium metal anodes. Herein, an in situ -formed flexible three-dimensional honeycomb-like poly(2, 2, 2-trifluoroethyl methacrylate) film (PTFEMA) fabricated by cross-linking lithium nitrate was designed to construct a LiF/Li3 N-enriched hybrid organic–inorganic interphase. The predominant species in the hybrid organic–inorganic interphase should possess excellent chemical stability against the Li metal anode in theory according to the calculation results of the higher LUMO energy level and larger LUMO–HOMO gap, which can regulate uniform Li deposition and the growth of large crystalline grains of Li. As a result, the hybrid organic–inorganic interphase achieved excellent reversibility (>98% Coulombic efficiency over 400 cycles) and an ultralow overpotential (about 10 mV) over 1000 h. Meanwhile, the LFP cathode with the developed anode achieved an 89.6% capacity retention after 500 cycles even at a high rate of 10 C. Moreover, the PTFEMA-N film showed hydrophobic but electrolyte wettable features. We hope this study can be applied to next-generation high-energy storage batteries for practical applications in the foreseeable future.